Programmatic Assessment in Medical Education: A Bibliometric and Narrative Review of Its Potential Contributions to Health Literacy and Health Promotion Competencies - N Juni Triastuti; Tri Nur Kristina; Titi Savitri Prihatiningsih (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Programmatic assessment (PA) has emerged as a transformative framework in medical education, emphasizing longitudinal evaluation, meaningful feedback, and data-informed decision-making to enhance learner development. Its role extends beyond competency measurement, contributing to broader educational goals such as strengthening health literacy and health promotion competencies—core attributes for future healthcare professionals. This bibliometric and narrative review aimed to map global research trends, influential contributors, and thematic patterns in programmatic assessment while synthesizing evidence on its potential to advance health literacy and health promotion competencies in medical education. Methods: A comprehensive search was conducted in Scopus database for articles published between 1977 and 2025. Inclusion criteria of eligible studies were those addressing programmatic assessment in medical or health professions education—including portfolios, decision processes, or programmatic feedback—and explicitly linking these approaches to health literacy or health promotion competencies. The dataset comprised 822 records and a final sample of 166 publications eligible for bibliometric analysis. Bibliometric indicators were analysed using VOSviewer, including publication trends, author networks, organizational and country contributions, and keyword co-occurrence. Narrative synthesis integrated empirical findings on PA implementation and its educational outcomes. Results: A total of 1092 authors, 502 organizations, and 44 countries contributed to 1737 indexed keywords, of which 167 met inclusion thresholds. Thematic clustering identified four dominant domains: feedback and learning analytics, competency-based assessment, digital and AI-supported assessment, and professional identity formation. Recent literature emphasizes PA’s capacity to cultivate reflective practice, communication skills, and health advocacy—key components of health literacy and promotion. Conclusion: Programmatic assessment represents an integrative and evidence-driven approach that not only enhances learning and assessment quality but also fosters essential competencies in health literacy and promotion, aligning medical education with 21st-century public health priorities.